Genetic Polymorphisms of the Human PNPLA3 Gene Are Strongly Associated with Severity of Non-Alcoholic Fatty Liver Disease in Japanese - Kawaguchi, Takahisa; Sumida, Yoshio; Umemura, Atsushi; Matsuo, Keitaro; Takahashi, Meiko; Takamura, Toshinari; Yasui, Kohichiroh; Saibara, Toshiji; Hashimoto, Etsuko; Kawanaka, Miwa; Watanabe, Sumio; Kawata, Sumio; et al. (PLOS ONE, 2012)
Background Nonalcoholic fatty liver disease (NAFLD) includes a broad range of liver pathologies from simple steatosis to cirrhosis and fibrosis, in which a subtype accompanying hepatocyte degeneration and fibrosis is classified as nonalcoholic steatohepatitis (NASH). NASH accounts for approximately 10–30% of NAFLD and causes a higher frequency of liver-related death, and its progression of NASH has been considered to be complex involving multiple genetic factors interacting with the environment and lifestyle. Principal Findings To identify genetic factors related to NAFLD in the Japanese, we performed a genome-wide association study recruiting 529 histologically diagnosed NAFLD patients and 932 population controls. A significant association was observed for a cluster of SNPs in PNPLA3 on chromosome 22q13 with the strongest p-value of 1.4×10−10 (OR = 1.66, 95%CI: 1.43–1.94) for rs738409. Rs738409 also showed the strongest association (p = 3.6×10−6) with the histological classifications proposed by Matteoni and colleagues based on the degree of inflammation, ballooning degeneration, fibrosis and Mallory-Denk body. In addition, there were marked differences in rs738409 genotype distributions between type4 subgroup corresponding to NASH and the other three subgroups (p = 4.8×10−6, OR = 1.96, 95%CI: 1.47–2.62). Moreover, a subgroup analysis of NAFLD patients against controls showed a significant association of rs738409 with type4 (p = 1.7×10−16, OR = 2.18, 95%CI: 1.81–2.63) whereas no association was obtained for type1 to type3 (p = 0.41). Rs738409 also showed strong associations with three clinical traits related to the prognosis of NAFLD, namely, levels of hyaluronic acid (p = 4.6×10−4), HbA1c (p = 0.0011) and iron deposition in the liver (p = 5.6×10−4). Conclusions With these results we clearly demonstrated that Matteoni type4 NAFLD is both a genetically and clinically different subset from the other spectrums of the disease and that the PNPLA3 gene is strongly associated with the progression of NASH in Japanese population.